Enhanced bacteriostasis and osseointegrative properties of SiRNA-modified polyetheretherketone surface for implant applications. - Zhen Liu; Libin Yang; Yazhuo Ni; Keying Chen; Qiquan Yan; Zhiying Zhao; Bo Xu; Yaoyang Li; Rui Li; Jianwen Li (PLoS ONE)
Polyetheretherketone (PEEK), bearing an elastic modulus that effectively simulates the innate properties of natural bone, has come into the spotlight as a promising bone substitute material. Nonetheless, the biologically inert nature of PEEK, combined with its insubstantial osseointegration and sterilization capabilities, pose constraints on its clinical application in the realm of implants. RNA interference (RNAi), an effective technique used for gene expression regulation, has begun to be applied in implant surface modification. Herein, siCKIP-1 is securely affixed to the surface of PEEK implants, aided by an antibacterial polyphenol tannic acid (pTAN) coatings, enhancing physiologic osseointegration and inhibiting bacterial infection. This method breakthrough not merely facilitates the convenience, but also multifaceted PEEK implants' refinements. The modified PEEK implants have impressive biocompatibility coupled with a noteworthy degree of antibacterial properties. Meanwhile, modified PEEK implants improved osteogenic differentiation of rat bone mesenchymal stem cells (rBMSCs) and demonstrated excellent osteointegrative properties in rat femur implantation models. Therefore, identifying a new implant material with excellent biocompatibility and biomechanical properties is essential.